Primary user emulation attack mitigation using neural network. (December 2020) - Ponnusamy, Vijayakumar; Kottursamy, Kottilingam; Karthick, T.; Mukeshkrishnan, M.B.; Malathi, D.; Ahanger, Tariq Ahamed
Highlights: Neural network based PUEA detection in real time on multiple frequencies using Software defined Radio (SDR) hardware USRP. A reliable spectrum sensing mechanism on multiple frequencies in the presence of PUEA attack on real time channel using SDR realization. Detecting PUEA attack using a neural network without the location information. Improving overall spectral utilization and spectral usage by CR. Abstract: The spectrum sensing scheme suffers from a physical layer attack of Primary User Emulation Attack (PUEA). The resolution is to mitigate the cognitive radio user from the PUEA under the physical layer. Detecting the PUEA attack in real-time is a challenging one. The traditional Location-based PUEA detection requires the primary user's location knowledge, which may not be possible practically. This research focuses on developing a reliable spectrum sensing mechanism in the presence of PUEA attack and rapid change in the wireless channel. This reliable spectrum sensing framework is developed using the neural network-based PUEA detector excluding the location information. The Software-Defined Radio (SDR) called Universal Software Radio Peripheral (USRP) 2943R is used to implement the proposed mechanism for analyzing performance in real-time. The real-time experimental results show that PUEA detection can be achieved with 97% accuracy. Graphical abstract: Image, graphical abstract